Morphometric Study of Cranial Bones in Japanese Quail Embryo; Coturnix japonica - Mahmood, Hawzhin Jamal; Salih, Kamal Ali (Sulaimani Journal for Pure and Applied Sciences, 2020)
Morphometric study of cranial bones had not studied well in avian; hence Japanese quail embryos were an important model in the developmental research because it had a short incubation period. In the current study, seventy fertilized eggs of Japanese quail collected, forty-two embryos used for anatomical study, and twenty-eight embryos used for histological study. The anatomical study demonstrated cranial bones consisted of two parts cranial base and cranial vault. On 3rd to 9th day of incubation, the cranial base chondrified to numbers of cartilage templates. On 10th to 13th day of incubation, these cartilages ossified and replaced by bones. In contrast cranial vault bones ossified directly from 8th to 10th day of incubation. Histological study displayed on 3rd to 9th day of incubation, cranial base chondrified through condensation and differentiation of mesenchymal cells areas to cartilage templates. On 10th to 12th day of incubation, bone collar formed. On 12th to 14th day of incubation, endochondral ossification centers of all cranial base bones occurred. On 14th to 16th day of incubation, woven bones created. While, cranial vault bones developed through condensation and differentiation of mesenchymal cells to osteoblasts directly, and intramembranous ossification centers of all cranial vault bones formed from 8th to 10th day of incubation. On 12th to 16th day of incubation, woven bones created. The current study summarized chondrification and ossification of cranial bones of Japanese quail embryos.
Keywords: Coturnix japonica embryos; cranial bones; chondrification; and ossification